An Optimized Bacteriophage Cocktail Can Effectively Control Salmonella in vitro and in Galleria mellonella - Nale, Janet Y.; Vinner, Gurinder K.; Lopez, Viviana C.; Thanki, Anisha M.; Phothaworn, Preeda; Thiennimitr, Parameth; Garcia, Angela; AbuOun, Manal; Anjum, Muna F.; Korbsrisate, Sunee; Galyov, Edouard E.; Malik, Danish J.; et al. (Frontiers in Microbiology, 2021)
Salmonella spp. is a leading cause of gastrointestinal enteritis in humans where it is largely contracted via contaminated poultry and pork. Phages can be used to control Salmonella infection in the animals, which could break the cycle of infection before the products are accessible for consumption. Here, the potential of 21 myoviruses and a siphovirus to eliminate Salmonella in vitro and in vivo was examined with the aim of developing a biocontrol strategy to curtail the infection in poultry and swine. Together, the phages targeted the twenty-three poultry and ten swine prevalent Salmonella serotype isolates tested. Although individual phages significantly reduced bacterial growth of representative isolates within 6 h post-infection, bacterial regrowth occurred 1 h later, indicating proliferation of resistant strains. To curtail bacteriophage resistance, a novel three-phage cocktail was developed in vitro, and further investigated in an optimized Galleria mellonella larva Salmonella infection model colonized with representative swine, chicken and laboratory strains. For all the strains examined, G. mellonella larvae given phages 2 h prior to bacterial exposure (prophylactic regimen) survived and Salmonella was undetectable 24 h post-phage treatment and throughout the experimental time (72 h). Administering phages with bacteria (co-infection), or 2 h post-bacterial exposure (remedial regimen) also improved survival (73–100% and 15–88%, respectively), but was less effective than prophylaxis application. These pre-livestock data support the future application of this cocktail for further development to effectively treat Salmonella infection in poultry and pigs. Future work will focus on cocktail formulation to ensure stability and incorporation into feeds and used to treat the infection in target animals.